2021
DOI: 10.15537/smj.2021.42.10.20210396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of COVID-19 mortality in Saudi Arabia

Abstract: Objectives:To analyze the clinical and epidemiological characteristics for 224 of in-hospital coronavirus disease 2019 )COVID-19( mortality cases. This study's clinical implications provide insight into the significant death indicators among COVID-19 patients and the outbreak burden on the healthcare system in the Kingdom of Saudi Arabia )KSA(. Methods:A multi-center retrospective cross-sectional study conducted among all COVID-19 mortality cases admitted to 15 Armed Forces hospitals across KSA, from March to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Poor outcome was observed in 18% (97/527) of patients, and the proportion of patients who died during admission was 8% (42/527). These findings are supported by previous national and international studies ranging from 6% to 33% for ICU admission and 6% to 14% for hospital mortality [11,12,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Poor outcome was observed in 18% (97/527) of patients, and the proportion of patients who died during admission was 8% (42/527). These findings are supported by previous national and international studies ranging from 6% to 33% for ICU admission and 6% to 14% for hospital mortality [11,12,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…According to the ndings, there were 54% more males than females who had COVID-19 infections. This is in line with research done in Saudi Arabia, where 63.4% of the sample members were men; research done in the United Arab Emirates, where 84.6% of the sample members were men; and research done in Iran, where 67.4% of the sample members were men [7][8][9]. In contrast, the study in Lebanon did not demonstrate a 51% rise in the incidence of male infection compared to 49% for females [10].…”
Section: Discussionsupporting
confidence: 86%
“…According to our study's ndings, patients over the age of 61 had a 31% infection rate for COVID-19 infection. These ndings are in line with research conducted in Saudi Arabia, where patients with COVID-19 had an average age of 69.6 years [7]. In a prior US study, individuals with COVID-19 who were brought to the critical care unit and whose average age was 70 years old saw a 67% increase in mortality [13,14].…”
Section: Discussionsupporting
confidence: 83%
“…Likewise, this study has found that the most prevalent comorbidities were diabetes mellitus (73.7%) followed by hypertension (69.6%) [15] . Another study done in Saudi Araba assessing the comorbidities and risk factors for severe outcomes in COVID-19 patients, found that mortality rate of COVID-19 was significantly higher among patients with respiratory, cardiovascular, neurological, and renal comorbidities [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study further asserts that given the presence of either one comorbidity or more, hypertension, or a chronic respiratory condition; one can predict that a HCW infected with COVID-19 will end up admitted in ICU. Two studies, one conducted in Saudi Arabia and one in Egypt, asserted that on addition to these three factors, renal impairment is also a significant predictor of ICU admission among COVID-19 patients [16] , [17] …”
Section: Discussionmentioning
confidence: 99%